PENGARUH KEMAMPUAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI KECAMATAN GAYAMSARI KOTA SEMARANG - Putra, Dana Cahya; Mustam, Muhammad; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2013)
In order to support the achievement of performance accountability Semarang regency government better by improving the performance of civil servants who are in the local government area in Semarang. The study aims to describe the performance of employees and determine the influence of environmental variables and the ability to work on the performance of employees working in the District Gayamsari Semarang. Employee performance is a process of assessment of the progress of the work against the goals and objectives in the management of human resources in achieving organizational goals. According to Armstrong there are four factors related to the performance of one's work environment, style of leadership, productivity, and interpersonal skills. Whereas performance by Surya Dharma theory is a theory of motivation, the concept of organizational effectiveness, confidence managing performance, work environment. This study has a locus in the District Gayamsari the city, it is because there is an indication of less than optimal performance of employees in the agency. This type of research is explanatory, respondents drawn a number of 33 people by using population. This study uses quantitative data analysis and hypothesis testing using Rank Kendall, Kendall concordance coefficient and the coefficient of determination.The results showed the results of the performance of employees in the district of Semarang Gayamsari high of 15.2% and a high of 84.8%, the magnitude of the effect between the ability of the (X 1) on employee performance (Y) is equal to 27.56%, the level of influence between the work environment (X 2) on employee performance (Y) is equal to 24.21%, and Employee Performance (Y) is affected by the Work Capability (X 1) and Working Environment (X 2) jointly by 52.71%. From these results, the authors provide suggestions for service revenue and financial management in the form of improved employee performance is optimal, then the increase employability through the provision of training / skills training and work environment through improved infrastructure and create intimacy all employees.